Reduce the equation to simple form: ax + by = c , where a, b, c have no common factor.
Generally a, b, c are simple numbers and you wont have to do complex calculations.
(1) 2x - 6y - 1 = 3
=> 2x - 6y = 4 (make variables on one side and constant on the other)
=> x - 3y = 2 ( Cancel the common factor 2 from all the terms)
(2) 5x - 3 = 15y + 7
=> 5x -15y = 10
=> x - 3y = 2 ( Cancel the common factor 5 from all the terms)
"Appreciation is a wonderful thing. It makes what is excellent in others belong to us as well."
Press Kudos, if I have helped.